Remoção do ácido mefenâmico em água utilizando carvão ativado em pó, lama vermelha e oxidação com cloro - Moruzzi, Rodrigo B. [UNESP]; Lima, Verônica B. [UNESP]; Colombo, Renata; Conceição, Fabiano T. [UNESP]; Lanza, Marcos R. V. (Sociedade Brasileira de Química, 2014)
The use of activated carbon powder (ACP), red mud and oxidation with chlorine to remove mefenamic acid in water are described, aimed at their application as a complement to sewage treatment processes in Brazil. A study on the behavior of mefenamic acid in water was performed by evaluating its dissolution for different concentrations and times. Subsequently, the optimal conditions for removal of mefenamic acid were investigated using ACP adsorption at different pH and concentrations, and red mud adsorption using different pH. The utilization of different pH and times was also investigated to establish the ideal conditions for chemical oxidation of the drug. Among the different conditions studied, the best condition for drug removal by ACP and red mud were 100% and 96%, respectively, while the best condition for chemical oxidation occurred using solutions with pH 6 and 7 and reaction times of 30 and 60 minutes.
Mefenamic acid removal in water using activated carbon powder, red mud and oxidation with chlorine
Keywords: mefenamic acid; adsorption; oxidation